Campaign Preparation for Complex Initiatives: A Person-Centered Approach to Audience Segmentation of Parents' Antibiotic Stewardship. Issue 12 (2nd December 2018) - Smith, Rachel A.; MacGeorge, Erina L.; Hackman, Nicole M.; M'ikanatha, Nkuchia M.
ABSTRACT: The evolution of antibiotic resistance is outpacing the speed at which new antibiotics will reach the marketplace. To slow the rate of resistance, people need to engage in antibiotic stewardship, which includes acts to prevent the spread of bacteria and judicious use of antibiotics to treat infections. This study identified the patterns and predictors of antibiotic stewardship behaviors of parents ( N  = 516) related to their children. The latent class analysis revealed three profiles of parental stewardship, labeled Stewards, Requesters, and Non-Stewards. The findings implied different campaign goals: to encourage Stewards to follow through on their intentions, to encourage Requesters to stop asking providers for antibiotics when their children have ear infections, and to influence Non-Stewards to accept medical advice when an antibiotic is not indicated and to dispose of leftover antibiotics. The covariate analysis provided theoretical insight into the strategies to pursue in campaigns targeting these three groups. For example, parents who perceived antibiotic-resistant infections as less serious health conditions, felt less worry when thinking about their child getting an antibiotic-resistant infection, and had stronger misattributions of antibiotics' efficacy to treat multiple symptoms were more likely to be Requesters and Non-Stewards, instead of Stewards.